2019
DOI: 10.1002/advs.201900644
|View full text |Cite
|
Sign up to set email alerts
|

The Puzzle of the Walnut Shell: A Novel Cell Type with Interlocked Packing

Abstract: The outer protective shells of nuts can have remarkable toughness and strength, which are typically achieved by a layered arrangement of sclerenchyma cells and fibers with a polygonal form. Here, the tissue structure of walnut shells is analyzed in depth, revealing that the shells consist of a single, never reported cell type: the polylobate sclereid cells. These irregularly lobed cells with concave and convex parts are on average interlocked with 14 neighboring cells. The result is an intricate arrangement th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 18 publications
2
58
1
Order By: Relevance
“…Finally the much denser (brighter on the scans) and dry nutshell protects the seed, which is mostly surrounded by an empty cavity ( Figure 1A, Supplementary Movie 5). Zooming into the nutshell via x-ray tomography showed that the entire shell is composed of polylobate cells, each of which tightly interlocked with on average 14 neighbors (Antreich et al, 2019). While other nutshells, like Macadamia build up their cells with different cell types, i.e., fibers and sclerenchyma cells (Schuler et al, 2014), walnut relies only on the puzzle cell type (Antreich et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally the much denser (brighter on the scans) and dry nutshell protects the seed, which is mostly surrounded by an empty cavity ( Figure 1A, Supplementary Movie 5). Zooming into the nutshell via x-ray tomography showed that the entire shell is composed of polylobate cells, each of which tightly interlocked with on average 14 neighbors (Antreich et al, 2019). While other nutshells, like Macadamia build up their cells with different cell types, i.e., fibers and sclerenchyma cells (Schuler et al, 2014), walnut relies only on the puzzle cell type (Antreich et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although wood and nutshell have different mechanical functions, which are realized by isotropic puzzle cells (Antreich et al, 2019) for high compression forces and anisotropic fiber arrangement for high tensile strength respectively (Gibson, 2012), the underlying secondary cell wall and its maturation show common features.…”
Section: Maturation Of the Shell By Impregnation And Dehydrationmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] During development on the parental plant, individual layers of the pericarp or the testa may harden substantially via extensive secondary cell wall formation and lignification. [7,8] Cracking these shells after they have reached maturity requires remarkably high compression forces in some species, ranging from 300 to ≈700 N for pecans, walnuts, and hazelnuts; and up to ≈4000 N for macadamia shells. [9] In the natural environment, the encapsulated seed, known as the dispersal unit or diaspore, is typically dispersed by granivorous and scatter-hoarding animals.…”
Section: Doi: 101002/adma202004519mentioning
confidence: 99%